Ultrastrong duplex high-entropy alloy with 2 GPa cryogenic strength enabled by an accelerated martensitic transformation. (October 2019) - Kim, Dong Geun; Jo, Yong Hee; Yang, Junha; Choi, Won-Mi; Kim, Hyoung Seop; Lee, Byeong-Joo; Sohn, Seok Su; Lee, Sunghak
Abstract: The existing deformation-induced martensitic transformation mostly focuses on overcoming the trade-off of cryogenic strength-ductility; however, an enhancement of cryogenic strength further is still challenging. We present a concept to yield a cryogenic strength of 2 GPa in a duplex V10 Cr10 Co30 Fe50 alloy. We adopt a thermodynamic calculation to reduce the stability of metastable face-centered-cubic (FCC) matrix, significantly promoting the martensitic transformation. In conjunction with the chemically driven promotion, the duplex structure including athermal body-centered-cubic (BCC) martensite enables mechanical strain partitioning to accelerate the transformation further. This finding could be an appropriate design strategy to develop new ultrastrong alloys for cryogenic applications. Graphical abstract: Unlabelled Image